Early Postnatal Care Service Utilization and Associated Factors among Mothers who Gave Birth in the Last One Year Preceding the Survey in Sidama Zone Malga District, Southern Ethiopia - Gebre, Gashawun; Kote, Mesfin; Kejela, Gemechu; Tunje, Abayneh (Ethiopian Journal of Reproductive Health, 2019)
BACKGROUND: Early Post-natal care service utilization is extremely low and stagnant over the decade of period in Ethiopia. Ethiopian Demographic and Health Survey 2016 reported that only 17% early post-natal care service utilization occurred despite the fact that, maternal mortality is high in the first 24 to 48 hours after delivery. OBJECTIVE: The aim of this study was to assess early postnatal care service utilization and associated factors among mothers who gave birth in the last one year, in Sidama Zone Malga Woreda, Southern Ethiopia. METHOD: A community based quantitative supplemented by a qualitative cross-sectional study was conducted from September 15, 2017 to October 15, 2017 in Sidama Zone, Malga district among 395 mothers who gave birth in the last one year. Mothers were selected by Simple random sampling technique. Quantitative data was collected by semi structured questionnaires and coded, cleaned, entered into EPI info version 3 and exported to SPSS version 20 for analysis. In binary logistic regression, variables with P value less than 0.25 were taken into multivariable logistic regression analysis and then, variables with p value < 0.05 at the final model were considered statistically significant predictors of the outcome variable. Qualitative data was collected by focus group discussions, and Individual Indepth interview and then thematic analysis were used to interpret the results. RESULTS: In this study, 22.5% of mothers utilized early postnatal care. Women who had experience of early postnatal care utilization has two times (AOR: 2.11, 95% CI: 1.11, 4.00), those who delivered at health facility were four times, (AOR: 4.10, 95% CI : 1.76, 9.57), those mothers who decide by themselves about early post-natal care utilization nearly four times (AOR: 3.84, 95% CI: 1.88, 7.82 ) , mothers who traveled on foot for less than two hours were four times (AOR: 4.24, 95% CI: 1.82, 9.91), mother who had four antenatal care follow up were nearly four times (AOR: 3.94, 95% CI: 1.18, 13.23) and educated mothers were seven times (AOR: 7.04, 95% CI: 2.42, 20.49) more likely to utilize early postnatal care service than their counterparts. CONCLUSION: The study revealed that, early postnatal care services in the district are low. Maternal education, place of delivery, decision making power of the mother, time taken to reach to health facility, antenatal care follow up, previous early postnatal care utilization and experience of the mother were independent predictors of early postnatal care service utilization. Therefore, Social and behavioral change communication strategies and continuum of community based care should have to strengthened. KEY WORDS: Early Post-natal care, utilization, Barrier, Associated factor, Malga district